Structural conditions required for the bridge lithiation and substitution of a basic calix[4]arene - Fischer, Conrad; Seichter, Wilhelm; Weber, Edwin (Beilstein Journal of Organic Chemistry, 2011)
Lithiation and subsequent reaction with CO2 was applied to calix[4]arenes with different, equal or mixed, ether functions at the lower-rim site as well as tert-butylated or non-tert-butylated upper-rim positions. Whereas this reaction fails for symmetric calix[4]arene ethers with alkoxy residues greater than methoxy, the carboxylation of mixed methoxy-propoxy calixarene ethers is possible. In connection with this, several new monobridge-substituted calix[4]arenes were characterized with respect to their conformational behaviour in solution and the X-ray crystal structure of one key intermediate is taken into consideration.
Keywords: calixarene; lithiation; methylene bridge; supramolecular chemistry; X-ray structure